The Effects of Yoga on Physical Activity and Respiratory Health in Duchenne Muscular Dystrophy: A Literature Review - Frączek, Karolina; Janaszek, Agnieszka; Strzępek, Aleksandra; Kałuża, Kinga; Chmurska, Agnieszka; Majchrzyk, Aleksandra; Łyżwa, Julia; Pater, Michał; Kałwa, Natalia; Smerdzyński, Mateusz (Journal of Education, Health and Sport, 2026)
Purpose: Duchenne muscular dystrophy (DMD) is a progressive neuromuscular disorder characterized by declining motor performance and respiratory function. The aim of this study was to evaluate current scientific evidence on the effects of yoga-based interventions on physical activity and pulmonary function in individuals with DMD. Materials and Methods: A narrative literature review was conducted using PubMed and Google Scholar databases. The search included studies published between 2000 and 2026 focusing on Duchenne muscular dystrophy, rehabilitation, respiratory function, physical activity, and yoga-based interventions. Articles were screened according to their relevance to yoga-based rehabilitation approaches in patients with DMD. Results: The reviewed studies indicate that yoga interventions may improve functional capacity, balance, and tolerance for daily activities in children with DMD. Programs combining adapted postural exercises (asanas), breathing techniques (pranayama), and relaxation practices were associated with improved pulmonary function parameters and autonomic regulation, including increased heart rate variability. Yoga programs were generally safe and well tolerated. Conclusions: Yoga may be a supportive component of multidisciplinary rehabilitation in DMD. It may contribute to improved respiratory function, functional performance, and overall well-being. Further large-scale studies with standardized protocols are needed to confirm long-term clinical benefits.